Ketidaksantunan Berbahasa Di Media Sosial: Kajian Pragmatik Terhadap Kasus Dwi Sasetyaningtyas - Try Widya Andini; Naina Ikhdina Hapiz; Qesya Balqis Lubis; Zaskia Putri Andari; Shintya Akrima; Herning Puspitarini (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2026)
The phenomenon of communication on social media often gives rise to various forms of linguistic impoliteness influenced by emotional factors, freedom of expression, and the lack of social control. One case that attracted public attention is the statement made by Dwi Sasetyaningtyas, an alumna and recipient of the LPDP scholarship, which went viral and triggered diverse responses from the public. This study aims to analyze the implicatures, speech acts, and forms of linguistic impoliteness that emerge in online discussions related to the case. The method used is qualitative with a descriptive approach. The data were obtained from posts and comments on social media related to the phenomenon, and then analyzed using a pragmatic framework. The results show that linguistic impoliteness appears in the form of direct accusations, insults, sarcasm, and the use of emotional language. In addition, implicatures were found that imply criticism toward the individuals involved, as well as various types of speech acts, such as expressive, directive, and declarative. These findings indicate that communication on social media not only functions as a means of conveying information but also as a space for expressing opinions that can potentially lead to conflict if not accompanied by an awareness of linguistic ethics.